Solve: x^2 + x + 1 = 0

This answer is restricted. Please login to view the answer of this question.

Login Now

Solution:

The above equation is of the form of

ax2 + bx + c = 0

where, a = 1, b = 1 and c = 1

Here, x = \(\frac{-b \pm \sqrt{b^2 – 4ac}}{2a}\)

Putting the values of a, b and c

x = \(\frac{-1 \pm \sqrt{1^2 – 4 \times 1 \times 1}}{2 \times 1}\)

= \(\frac{-1 \pm \sqrt{1 – 4}}{2}\)

= \(\frac{-1 \pm \sqrt{-3}}{2}\)

= \(\frac{-1 \pm \sqrt{3} \times \sqrt{-1}}{2}\)

= \(\frac{-1 \pm \sqrt{3} i}{2}\)

If you found any type of error on the answer then please mention on the comment or report an answer or submit your new answer.
Leave your Answer:

Click here to submit your answer.

Discussion
0 Comments
  Loading . . .